Comparative tribology II–Measurable biphasic tissue properties have predictable impacts on cartilage rehydration and lubricity. (15th January 2022) - Kupratis, Meghan E.; Gure, Ahmed E.; Benson, Jamie M.; Ortved, Kyla F.; Burris, David L.; Price, Christopher
Abstract: Healthy articular cartilage supports load bearing and frictional properties unmatched among biological tissues and man-made bearing materials. Balancing fluid exudation and recovery under loaded and articulated conditions is essential to the tissue's biological and mechanical longevity. Our prior tribological investigations, which leveraged the convergent stationary contact area (cSCA) configuration, revealed that sliding alone can modulate cartilage interstitial fluid pressurization and the recovery and maintenance of lubrication under load through a mechanism termed 'tribological rehydration.' Our recent comparative assessment of tribological rehydration revealed remarkably consistent sliding speed-dependent fluid recovery and lubrication behaviors across femoral condyle cartilage from five mammalian species (equine/horse, bovine/cow, porcine/pig, ovine/sheep, and caprine/goat). In the present study, we identified and characterized key predictive relationships among tissue properties, sliding-induced tribological rehydration, and the modulation/recovery of lubrication within healthy articular cartilage. Using correlational analysis, we linked observed speed-dependent tribological rehydration behaviors to cartilage's geometry and biphasic properties (tensile and compressive moduli, and permeability). Together, these findings demonstrate that easily measurable biphasic tissue characteristics ( e.g., bulk tissue material properties, compressive strain magnitude, and strain rates) can be used to predict cartilage's rehydration and lubricating abilities, and ultimately its function in vivo . Statement of significance: In healthy cartilage, articulation recovers fluid lost to static loading thereby sustaining tissue lubricity. Osteoarthritis causes changes to cartilage composition, stiffness, and permeability associated with faster fluid exudation and presumably poorer frictional outcomes. Yet, the relationship between mechanical properties and fluid recovery during articulation/sliding remains unclear. Through innovative, high-speed benchtop sliding and indentation experiments, we found that cartilage's tissue properties regulate its exudation/hydration under slow sliding speeds but have minimal effect at high sliding speeds. In fact, cartilage rehydration appears insensitive to permeability and stiffness under high fluid load support conditions. This new understanding of the balance of cartilage exudation and rehydration during activity, based upon comparative tribology studies, may improve prevention and rehabilitation strategies for joint injuries and osteoarthritis. Graphical abstract: Image, graphical abstract